2022
DOI: 10.2106/jbjs.cc.22.00494
|View full text |Cite
|
Sign up to set email alerts
|

Transsacral Canal Plasty for Decompression of Lumbar Spinal Stenosis in a Patient With Epidural Lipomatosis

Abstract: Case: A 58-year-old man presented with lumbar spinal stenosis due to epidural lipomatosis. He underwent transsacral canal plasty (TSCP), in a manner similar to epidural adhesiolysis, which can be performed under local anesthesia. His leg pain improved dramatically in the year after surgery. Furthermore, magnetic resonance images during this time show neural decompression by reduction of the amount of epidural fat.Conclusion: TSCP was found not only to relieve pain but also to achieve neural decompression in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Unlike conventional catheters such as the Racz, the catheter used for TSCP (myeloCath®, Biomedica Healthcare Ltd., Tokyo, Japan) ( 8 ) is movable with excellent operability and followability, and mechanical adhesiolysis is possible by simply moving it from side to side ( 13 ). Data from collaborative studies at other institutions have shown that TSCP improves back and leg pain regardless of whether the patient has had previous spine surgery and that it may be a treatment option for elderly and immunocompromised patients for whom multiple surgeries are not recommended ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Unlike conventional catheters such as the Racz, the catheter used for TSCP (myeloCath®, Biomedica Healthcare Ltd., Tokyo, Japan) ( 8 ) is movable with excellent operability and followability, and mechanical adhesiolysis is possible by simply moving it from side to side ( 13 ). Data from collaborative studies at other institutions have shown that TSCP improves back and leg pain regardless of whether the patient has had previous spine surgery and that it may be a treatment option for elderly and immunocompromised patients for whom multiple surgeries are not recommended ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, there are previous reports indicating that dural sac area is a more sensitive measurement parameter than spinal canal area ( 31 ) and that a narrow dural sac area on magnetic resonance images is associated with leg pain at 1 year after lumbar spine surgery ( 32 ). Further, in view of a report suggesting that stenosis caused by epidural lipomatosis can be relieved by dissection of adhesions ( 13 ), the presence or absence of epidural lipomatosis was also selected as a factor. Other limitations of this study are that not all factors were included in the multivariate analysis and collinearity between factors could not be considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations